Change of Left Ventricular Myocardial Contractility in Speckle Tracking Echocardiography After Transjugular Intrahepatic Portosystemic Shunt Predicts Survival - Jansen, Christian; Nordmann, Pia; Cremonese, Carla; Praktiknjo, Michael; Chang, Johannes; Lehmann, Jennifer; Thomas, Daniel; Nickenig, Georg; Weber, Marcel; Stöhr, Elisabeth; Öztürk, Can; Zachoval, Christian; et al. (Frontiers in Gastroenterology, 2022)
Background: Left ventricular global longitudinal strain (LV-GLS) has been shown to better reflect the left cardiac contractility in cirrhosis than other investigations and might bear prognostic value. The aim of this study was to investigate the evolution of myocardial contractility assessed by speckle tracking echocardiography (STE) after transjugular intrahepatic portosystemic shunt (TIPS) placement and its prognostic value in outcome. Methods: In this study, 206 (126 males) patients with liver cirrhosis receiving TIPS were included. In all study patients, conventional transthoracic echocardiography (TTE) was performed before and in the first weeks after TIPS placement to assess left and right ventricular volume, planar and functional parameters. Also, LV-GLS was measured by STE to assess left ventricular contractility as surrogate for myocardial dysfunction. Hemodynamic and clinical parameters were assessed before TIPS and during follow-up. Results: As expected, most conventional parameters of TTE showed a significant change after TIPS placement. However, neither the absolute values, nor the changes of conventional cardiac parameters of TTE before and after TIPS insertion were associated with survival. By contrast, an increase in contractility of more than 20% using STE after TIPS was an independent predictor of mortality. Conclusion: These results demonstrate that an increase of left ventricular contractility of more than 20% after TIPS insertion is an independent predictor of survival and this may identify patients at risk and in need of closer follow-up care.